Religious Tolerance Base on Local Wisdom in Indonesia - Dhani, Ahmad (PT. Riset Press International, 2023)
Tolerance is an effort made by religious people to respect and respect each other's beliefs. The people of Lombok with a multicultural religion prioritize the principle of tolerance through existing local wisdom. The approach used in this research is a qualitative approach with descriptive analysis method. The results of this study reveal that local-based tolerance is practiced by religious communities in Lombok as shown in community religious activities that involve adherents of other religions to participate in their religious practices. Such as Christmas, 'Eid al-Fitr, Vesak celebrations, and other religious practices. Lombok's Muslim community does not hesitate to invite non-Muslim neighbors to join in enlivening the halal bi halal event, the Prophet's birthday and other celebrations, Hindus also invite their neighbors to join in enlivening the ogoh-ogoh event which is their routine religious event, Christians also share and invited his neighbors to join in celebrating their Christmas event. So that tolerance in the local wisdom of the Lombok people is based on three aspects, namely Solidarity, mutual cooperation, and deliberation. These three things are the local culture of the community which has been practiced for generations, in order to achieve a harmonious and orderly life.